Pengaruh Sektor Pariwisata Terhadap Pertumbuhan Ekonomi Sumatera Barat - Silvi Algazali; Mike Triani (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to analyze the influence of the tourism sector on economic growth in West Sumatra Province. In this study, the variables used include domestic tourist visits, the number of accommodations in non-star hotels, and the number of restaurants. The data used are secondary data from 2017 to 2022, obtained from the Central Statistics Agency of West Sumatra Province. The analysis method applied is panel data regression with the Random Effect Model (REM) using E-views 12 software. The results of the study show that domestic tourist visits and accommodations in non-star hotels have a positive and significant effect on economic growth, while the number of restaurants does not have a significant effect. The coefficient of determination of 36.95% indicates that the independent variables are able to explain the economic growth variables in West Sumatra. This study suggests that local governments should maximize the potential of the tourism sector as a strategy to increase regional economic growth.